Aktivitas antibakteri ekstrak rimpang Jeringau (Acorus calamus L.) terhadap pertumbuhan Staphylococcus aureus dan Escherichia coli - Ari Hepi Yanti, Anisah, Siti Khotimah, (Jurnal Protobiont, 2014)
Jeringau (Acorus calamus L.) is an herb that is used to treat diarrhea, tapeworm and dysentery. If it is mixed with several other materials, it can help women after they are giving birth. This study was done to evaluate A. calamus’s antibacterial activity to inhibit the growth of Staphylococcus aureus and Escherichia coli. Ethanol and water were used as solvents to extract the Jeringau’s rhizome. The method used to test the antibacterial activity performance was the paper disk diffusion method in 25%, 50%, 75% and 100% v/v (ml/ml). The positive control was cloramphenicol, and the negative control was aquades. Based on the fitochemical test, A. calamus’s extract contained secondary metabolites compounds, such as alkaloid, flavonoid and polifenol. The results showed that there were inhibitions activities from the ethanol and water extract toward both of the tested bacteria. Water extract had smaller inhibition zone compared tto the ethanol. Different types and concentrations of solvents have different ability in inhibiting the growth of S. aureus and E. coli. The 100% concentration of both ethanol and water extract performed the highest activity to inhibit each bacterium growth.